A mathematical model for cerebrovascular dynamics - Alptekin, Melis. (Thesis (M.S.)-Bogazici University. Institute of Biomedical Engineering, 2010., 2010)
Human brain goes through a number of physiological changes in daily life. Some of these changes can be observed with optical imaging methods at near infrared light range. The aim of this study is, by using functional near infrared spectroscopy (fNIRS), with a speci c experimental protocol, estimating the venous compliance and resistance values of the brain by constructing a three-element Windkessel model and observing oxygenation and blood volume with respect to time. For this purpose, 10 healthy volunteers participated and measurements were taken from their prefrontal cortex during the experiment. When the subjects are in supine position, they were asked to move their heads down to their knees and they stayed in this position for 30 seconds. fNIRS signals were analysed to represent right and left hemisphere. Therefore, in each hemisphere, maximum and minimum points of blood volume showed no signi cant di erence for men and women. (left hemisphere: for Vmin; p=0.12, for Vmax; p=0.22; right hemisphere: for Vmin; p=0.073, for Vmax; p=0.074). Without taking sex di erence into account, Vmin and Vmax values of right and left hemisphere are not signi cantly di erent (respectively p=0.22, p=0.069). For compliance values, there is not a meaningful di erence between left and right hemisphere. (p= 0.38). For resistance values between right and left hemisphere, we found a signi cant di erence (p=0.04).Therefore, this study implies that there is not a meaningful di erence in a young subject group with respect to brain hemodynamics and parameters but only the resistance values. This model may be also used in an elderly or diseased group to observe brain hemodynamics.|Keywords: head-down tilt, fNIRS, Windkessel models
Keywords: Near infrared spectroscopy.